Aesthetic Orthodontics : An Overview - Patel, Dolly; Mehta, Falguni; Mehta, Nishit (Orthodontic Journal of Nepal, 2014)
Through the influence of the media and increasing awareness amongst the people aesthetic concerns regarding orthodontic treatment have risen up. The adult orthodontic patients put higher demands for aesthetic results not only after the treatment but also during the treatment phase. Not only adults but all orthodontic patients give importance to their appearance and for social or work reasons would probably refuse visible orthodontic treatment therapy. This article describes some of the effective solutions to these problems that will not impair the patient from an aesthetic point of view during the treatment phase